South Saami - Ylikoski Jussi (Oxford University Press, 2025)
South Saami, an indigenous language spoken in the central regions of Norway and Sweden, is the westernmost variety of the westernmost (Saami) branch of the Uralic language family. Despite its long history in the immediate neighbourhood of Scandinavian languages, many of the core features of South Saami stand out as constituting a typologically unusual mixture that distinguishes the language from most western Uralic languages. Such features include, for example, a predominantly SOV word order and the marginal role of the copula. Within the Saami language chain in particular, the most remarkable feature of South Saami morphophonology is the complex metaphony in nominal and verbal inflection, while the consonant gradation typical of other Saami languages is absent in that language.
The Oxford Guide to the Uralic Languages